KELEKATAN (ATTACHMENT) DAN PEMBENTUKAN KARAKTER - Nurhidayah, Siti (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2011)
This article will explain about the attachment and character development. From this article it can be concluded that there are several factors that can affect a child's development, namely a factor from within, from outside the child and the interaction of both. The factors that originate from outside the mother's condition factors and environmental conditions. Behavior of parents, especially mothers considered to play an important role in child development because it plays an important role early in a child's life. Children get a first impression about the world through behavior and attitude of the mother /parents against children, especially in early age. If the mother applies to both the impression the child about the world and a positive environment and attitude of children will also be positive. This can cause the child to explore an optimal environment, consequently the development of behavioral, emotional, social, cognitive and personality of the child would be optimal as well.